2006
DOI: 10.1192/pb.30.11.419
|View full text |Cite
|
Sign up to set email alerts
|

Capacity to consent to treatment in patients with acute mania

Abstract: Aims and MethodThis study aimed to determine the proportion of patients hospitalised with mania who had capacity to consent to treatment, to determine the predictors of capacity and to explore the relationship between detained status and capacity. Fifty in-patients with mania participated in a clinical interview to assess capacity.ResultsNineteen patients (38%) had overall capacity. Capacity was predicted by higher IQ, lower severity of manic symptoms and more episodes of depression; it was not related to volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Loss of DMC-T is extremely common in mania, probably more so than for any other psychiatric condition, and is often regained in about a month ( Owen et al, 2011 ). Several studies have concluded that the majority of manic inpatients are lacking in DMC-T ( Beckett & Chaplin, 2006; Cairns et al, 2005a; Owen et al, 2008 ). The most recent of these, which involved clinical interviews and structured DMC-T assessment, reported that 97% of those admitted with mania to a psychiatric ward, whether formally or informally, had impaired DMC-T ( Owen et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of DMC-T is extremely common in mania, probably more so than for any other psychiatric condition, and is often regained in about a month ( Owen et al, 2011 ). Several studies have concluded that the majority of manic inpatients are lacking in DMC-T ( Beckett & Chaplin, 2006; Cairns et al, 2005a; Owen et al, 2008 ). The most recent of these, which involved clinical interviews and structured DMC-T assessment, reported that 97% of those admitted with mania to a psychiatric ward, whether formally or informally, had impaired DMC-T ( Owen et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen devised assessments of capacity for a specific procedure, for instance capacity to consent to electroconvulsive therapy, having a blood test or admission to a psychiatric ward (Appelbaum et al , 1981, 1998; Roth et al , 1982; Norko et al , 1990; Grisso & Appelbaum, 1991; Janofsky et al , 1992; Bean et al , 1994, 1996; Poythress et al , 1996; Tomoda et al , 1997; Paul & Oyebode, 1999; Wong et al , 2000, 2005; Vollmann et al , 2003). Sixteen (Hoffman & Srinivasan, 1992; Grisso et al , 1997; Melamed et al , 1997; Tomoda et al , 1997; Kitamura et al , 1998; Palmer et al , 2002; Bellhouse et al , 2003 a , b ; Lapid et al , 2003; Vollmann et al , 2003; Cairns et al , 2005 a , b ; Howe et al , 2005; Jacob et al , 2005; Koren et al , 2005; Beckett & Chaplin, 2006) used more flexible assessment methods, designed for use with any treatment decision. Studies generally framed capacity either in binary terms (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies (Bean et al , 1996; Tomoda et al , 1997; Vollmann et al , 2003; Vellinga et al , 2004; Cairns et al , 2005 b ; Beckett & Chaplin, 2006) assessed agreement between an interviewer performing a structured or semi-structured mental capacity assessment and a clinician's view of the patient's mental capacity. The kappa values ranged from ‘slight’ to ‘substantial’, (median κ=0.45, IQR 0.39–0.66).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include a measure of symptom severity or psychopathology. Previous research has shown that symptom severity and the presence of positive psychotic symptoms are associated with lack of capacity to make treatment decisions (Wong et al, 2005, Beckett andChaplin, 2006). Although the MacCAT-T has been used in individuals with cognitive impairment, it can be difficult to use in those with severe dementia (Vollmann et al, 2003).…”
Section: Limitationsmentioning
confidence: 99%